2019
DOI: 10.1002/adma.201903173
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Utilization in Semitransparent Organic Photovoltaics Using an Optical Outcoupling Architecture

Abstract: Building-integrated photovoltaics employing transparent photovoltaic cells on window panes provides an opportunity to convert solar energy to electricity rather than generating waste heat. In this work, we demonstrate semitransparent organic photovoltaic cells (ST-OPVs) that utilize a non-fullerene acceptor based near-infrared (NIR) absorbing ternary cell combined with a thin, semitransparent, high conductivity Cu-Ag alloy electrode. A This article is protected by copyright. All rights reserved. 2 combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 37 publications
0
112
0
Order By: Relevance
“…By its spectral filtering capability, good electrical conductivity, and large‐scale manufacturing compatibility, the MDM‐based filters can be employed as semitransparent electrodes in various optoelectronic devices, such as solar cells with colored appearances [ 285–289 ] and light emitting diodes with modified emission properties. [ 290 ] The schematic of a colored perovskite solar cell using a Ag/ITO/Ag top electrode is shown in Figure 25d.…”
Section: Device Applicationsmentioning
confidence: 99%
“…By its spectral filtering capability, good electrical conductivity, and large‐scale manufacturing compatibility, the MDM‐based filters can be employed as semitransparent electrodes in various optoelectronic devices, such as solar cells with colored appearances [ 285–289 ] and light emitting diodes with modified emission properties. [ 290 ] The schematic of a colored perovskite solar cell using a Ag/ITO/Ag top electrode is shown in Figure 25d.…”
Section: Device Applicationsmentioning
confidence: 99%
“…Benefiting from the improvement in light transmittance, a relatively high AVT of 26.2% was obtained. Li et al 98 used an antireflection coating (ARC) and an optical outcoupling (OC) architecture to enhance light utilization in the semitransparent device based on PCE‐10:TT‐FIC:BT‐CIC. The UV‐vis spectrum showed that the main absorption region of the ternary film is located at 600–1000 nm, leaving a transparent window between 400 and 600 nm.…”
Section: Optical Management In Semitransparent Organic Photovoltaicsmentioning
confidence: 99%
“…Li et al adopted a outcoupling layer of 4,4′‐bis( N ‐carbazolyl)‐1,1′‐biphenyl (CBP)/MgF 2 /CBP/MgF 2 with a multilayer SiO 2 /SiN x DBR and an antireflection coating to improve the degree of light manipulation (Figure 3c ) . [ 83 ] They obtained a maximum LUE of 3.56 ± 0.11%, a PCE of 8.0 ± 0.2%, CIE coordinates of (0.337, 0.349), and a CRI of 87. Very recently, Forrest and coworkers prepared an ST‐OPV providing a PCE of 10.8% and visible transparency of ≈50%.…”
Section: Semitransparent Opvs and Pscsmentioning
confidence: 99%
“…Plot of PCE with respect to AVT for ST‐OPVs and ST‐PSCs reported in the literature. [ 1,9–12,15,17,18,20–22,24,33–110 ] …”
Section: Introductionmentioning
confidence: 99%